2006
DOI: 10.1080/01919510600704957
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Active Oxidant Species by Pulsed Dielectric Barrier Discharge in Water-Air Mixtures

Abstract: Experimental research into the electrical and optical parameters of pulsed dielectric barrier discharge (PDBD) was undertaken. PDBD was applied to humid air containing water droplets as a means of water oxidative treatment with short-living species generated in the discharge zone. In spectral analysis of PDBD, only small concentrations of nitric oxides were detected at the resulting electric field strength and electron mean energy sufficient for generation of OH-radicals. The water droplets served as electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Recently, a few studies have reported that gas-phase pulsed corona discharges could be used to generate OH • radical, in addition to O 3 , effectively using air containing water vapor as the gas source [22][23][24][25], and the concentration of OH • radical generated was found to be several times higher than that of O 3 [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few studies have reported that gas-phase pulsed corona discharges could be used to generate OH • radical, in addition to O 3 , effectively using air containing water vapor as the gas source [22][23][24][25], and the concentration of OH • radical generated was found to be several times higher than that of O 3 [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Application of optical fiber, lenses and collimators allowed us to obtain spectra of the plasma plume light emission at different locations with respect to the open end of the plasma gun. In these experiments the target placed at different distances from the open end of the plasma gun, was either dry or wet [37,38]. In general, different spectral lines of excited hydrogen, oxygen, nitrogen were detected [39].…”
Section: Resultsmentioning
confidence: 99%
“…The value of the capacitance obtained due to the simulation is a good estimation of its analytical counterpart obtained in [4] by the hybrid technique which involved the method of the integral equation and the method of Green function С = 1.74⋅10 -10 F/m. Let us note that the symmetric distribution of the electrostatic field allows us to determine the local capacities.…”
Section: Calculation Of the Electrostatic Fieldmentioning
confidence: 90%